The paradox: Ischemic cerebrovascular accidents and obesity – A retrospective Nationwide inpatient study. (May 2021) - Shaka, Hafeez; El-Amir, Zain; Wani, Farah; Dahiya, Dushyant Singh; Velazquez, Genaro Romero; Kichloo, Asim
Abstract: Introduction: Cerebrovascular accidents (CVAs) are a leading cause of neurological disability and mortality in older adults, with ischemic cerebrovascular accidents (ICVAs) accounting for around 80% of all CVAs. The aim of this study was to compare the outcomes of ICVAs in patients with obesity. Methods: This is a population-based retrospective observational study using data from the Nationwide Inpatient Sample. Hospitalizations involving ICVAs were studied with and without obesity. The primary outcome was inpatient hospital mortality. Results: The in-hospital mortality for hospitalizations with ICVAs was 4.1%. Patients with obesity had lower adjusted odds of in-hospital mortality (aOR: 0.85, 95% CI 0.79–0.93, p < 0.001) compared to Patients without obesity after multivariate logistic regression analysis. Obese patients had an increase mean LOS (0.2, 95% CI: 0.1–0.3 days, p < 0.001) and THC (3200, 95% CI: 2000–4400 US, p < 0.001) compared Patients without obesity. Conclusions: Patients who are admitted with ICVAs and obesity had lower in-hospital mortality compared to Patients without obesity. This adds to the body of knowledge for the obesity paradox among inpatient outcomes. Highlights: Obesity is a known risk factor for cardiovascular disease. Patients with obesity have ischemic strokes at a younger age on average compared to patients without obesity. After adjusting for confounders, patients with obesity had lower mortality following ischemic stroke.